Indigenous art and devotion on the Ruta de la Plata, Andean churches from the 17th-18th centuries - Pereira Campos, Magdalena (2013)
This article focuses on the cultural universe formed around the silver route, linking artistic and religious expressions that arose there. Collaboration and sharing practiced by indigenous communities before the arrival of the Spaniards made possible the construction and decoration of temples in this commercial circuit. In this sense, the Andean temples are a symbol of the strong relationship between different peoples, as well as their creativity and religiosity. Under Spanish rule, these communities adapted Western models, incorporating iconography and local ornaments. Finally, this South Andean Baroque style spread its influence to different places throughout the region, creating a valuable cultural universe.